Association of Patient-reported Experiences and Surgical Outcomes Among Group Practices: Retrospective Cohort Study. Issue 3 (March 2020) - Liu, Jason B.; Pusic, Andrea L.; Gibbons, Christopher J.; Opelka, Frank G.; Sage, Jill S.; Thompson, Vanessa M.; Ko, Clifford Y.; Hall, Bruce L.; Temple, Larissa K.
Abstract : Objective: The aim of the study was to determine the association of patient-reported experiences (PREs) and risk-adjusted surgical outcomes among group practices. Background: The Centers for Medicare and Medicaid Services required large group practices to submit PREs data for successful participation in the Physician Quality Reporting System (PQRS) using the Consumer Assessment of Healthcare Providers and Systems for PQRS survey. Whether these PREs data correlate with perioperative outcomes remains ill defined. Methods: Operations between January 1, 2014 and December 31, 2016 in the American College of Surgeons' National Surgical Quality Improvement Program registry were merged with 2015 Consumer Assessment of Healthcare Providers and Systems for PQRS survey data. Hierarchical logistic models were constructed to estimate associations between 7 subscales and 1 composite score of PREs and 30-day morbidity, unplanned readmission, and unplanned reoperation, separately, while adjusting for patient- and procedure mix. Results: Among 328 group practices identified, patients reported their experiences with clinician communication the highest (mean ± standard deviation, 82.66 ± 3.10), and with attention to medication cost the lowest (25.96 ± 5.14). The mean composite score was 61.08 (±6.66). On multivariable analyses, better PREs scores regarding medication cost, between-visit communication, and the composite score of experience were each associated with 4% decreased odds of morbidity [odds ratio (OR) 0.96, 95% confidence interval (CI) 0.92–0.99], readmission (OR 0.96, 95% CI 0.93–0.99), and reoperation (OR 0.96, 95% CI 0.93–0.99), respectively. In sensitivity analyses, better between-visit communication remained significantly associated with fewer readmissions. Conclusions: In these data, patients' report of better between-visit communication was associated with fewer readmissions. More sensitive, surgery-specific PRE assessments may reveal additional unique insights for improving the quality of surgical care. Abstract : Supplemental Digital Content is available in the text